Respuesta :
3(2x - 1) > = 4(2x - 3) - 3
6x - 3 > = 8x - 12 - 3
6x - 3 > = 8x - 15
6x - 8x > = -15 + 3
-2x > = -12
x < = -12/-2
x < = 6
the incorrect one is : A number line with a closed circle on 6, shading to the right
6x - 3 > = 8x - 12 - 3
6x - 3 > = 8x - 15
6x - 8x > = -15 + 3
-2x > = -12
x < = -12/-2
x < = 6
the incorrect one is : A number line with a closed circle on 6, shading to the right
Answer:
Option D). is the option.
Step-by-step explanation:
The given inequality is 3(2x - 1) ≥ 4(2x - 3) - 3
Now we will solve the inequality to get the answer.
3(2x -1) ≥ 4(2x - 3) - 3
6x - 3 ≥ 8x - 12 - 3 (distribution law)
6x -3 + 3 ≥ 8x - 12 - 3 + 3
6x ≥ 8x - 12
By adding 12 on both the sides
6x + 12 ≥ 8x -12 + 12
Now we will subtract 6x from both the sides
6x - 6x + 12 ≥ 8x -6x
12 ≥ 2x
2x/2 ≤ 12/2
x ≤ 6
So option D) A number line with a closed circle on 6 and shading to the right is incorrect. Rest all options are correct.